“Artists of Cameos” in Russia in the 1750s — Early 19th Century - Koroleva, Valeriia I. (Actual Problems of Theory and History of Art, 2015)
A new type of miniature profile portrait in the style of cameo arose and became widespread in the second half of the 18th century. Caused by the ideas of classicism, archaeological finds, and the interest in antiques, this kind of portraiture gained great popularity in Russia in the second half of the 18th – early 19th century. Despite the fact that numerous studies discuss portrait miniature, none of them is devoted to miniature-cameo portraits. The article is supposed to analyze the works of the artists who were specializing in cameo-styled miniatures. Based on the style, all the cameos mentioned in the article one could divide into several types: imitation of coins and medals or carved stone and sculptural relief, and following the patterns from easel painting, drawing, engraving, and porcelain painting.